Effects of mulching materials on the growth, development and yield of white yam - Osiru, D.; Hahn, S. (1994)
Two similar experiments are described in which the effects of different mulching materials and staking on the growth, development and yield of white yam (Dioscorea rotundata) Minisetts were studied. One white yam cultivar TDR 131 was used and the treatments were: black and white embossed polyethylene plastic (Visqeen 38mu) with either black or white surface up; light weight black polyethylene plastic; rice straw; staking but no mulch, and no staking and no mulch. Each experiment was laid out in a randomized complete block design with four replications. Polyethylene plastic mulch with white surface up was superior to all other treatments. Total dry matter per plant and total fresh tuber yield were all consistently higher in plants grown under the white surface polyethylene plastic mulch.